Penerapan Aplikasi Pegadaian Digital (PDS) dalam Pelayanan PT Pegadaian UPC Plasa Millenium Sebelum Dan Pada Masa Covid-19 - Widya Simanjuntak (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
In the current pandemic, direct transactions between companies and customers must be reduced to help the government suppress the spread of COVID-19. So that PT Pegadaian is more focused on marketing and sales activities on social media and applications that support every transaction with customers. However, direct transaction activities at pawn shops are still quite crowded by customers who want to make transactions. This study used descriptive qualitative method. This study uses primary data sourced from employees and customers of PT Pegadaian UPC Plasa Millennium. The use of the Digital Pegadaian (PDS) application in 2019 – 2020 has increased. Many customers know about the Digital Pegadaian (PDS) application at PT Pegadaian UPC Plasa Millennium. Some customers just download the app and don't use it at all. The PT Pegadaian UPC Plasa Millennium party improves education and services on how to use the Digital Procurement application as a non-cash payment tool during the covid-19 pandemic